Melatonin signaling in T cells: Functions and applications. Issue 3 (1st March 2017) - Ren, Wenkai; Liu, Gang; Chen, Shuai; Yin, Jie; Wang, Jing; Tan, Bie; Wu, Guoyao; Bazer, Fuller W.; Peng, Yuanyi; Li, Tiejun; Reiter, Russel J.; Yin, Yulong
Abstract: Melatonin affects a variety of physiological processes including circadian rhythms, cellular redox status, and immune function. Importantly, melatonin significantly influences T‐cell‐mediated immune responses, which are crucial to protect mammals against cancers and infections, but are associated with pathogenesis of many autoimmune diseases. This review focuses on our current understanding of the significance of melatonin in T‐cell biology and the beneficial effects of melatonin in T‐cell response‐based diseases. In addition to expressing both membrane and nuclear receptors for melatonin, T cells have the four enzymes required for the synthesis of melatonin and produce high levels of melatonin. Meanwhile, melatonin is highly effective in modulating T‐cell activation and differentiation, especially for Th17 and Treg cells, and also memory T cells. Mechanistically, the influence of melatonin in T‐cell biology is associated with membrane and nuclear receptors as well as receptor‐independent pathways, for example, via calcineurin. Several cell signaling pathways, including ERK1/2‐C/EBPα, are involved in the regulatory roles of melatonin in T‐cell biology. Through modulation in T‐cell responses, melatonin exerts beneficial effects in various inflammatory diseases, such as type 1 diabetes, systemic lupus erythematosus, and multiple sclerosis. These findings highlight the importance of melatonin signaling in T‐cell fate determination, and T cell‐based immune pathologies.